HBsAg level defines different clinical phenotypes of HBeAg(−) chronic HBV infection related to HBV polymerase-specific CD8+ cell response quality - Peña-Asensio, Julia; Calvo-Sánchez, Henar; Miquel-Plaza, Joaquín; Sanz-de-Villalobos, Eduardo; González-Praetorius, Alejandro; Delgado-Fernandez, Alberto; Torralba, Miguel; Larrubia, Juan-Ramón (Frontiers in Immunology, 2024)
Background HBe-antigen(Ag)-negative chronic hepatitis B virus (HBV) infection is characterized by little liver fibrosis progression and vigorous HBV-multispecific CD8+ T-cell response. Aims To assess whether HBsAg level could discriminate different HBeAg-negative chronic HBV infection subtypes with dissimilar quality of HBV-specific CD8+ T-cell response. Methods We recruited 63 HBeAg-negative chronic HBV infection patients in which indirect markers of liver inflammation/fibrosis, portal pressure, viral load (VL), and HBV-specific CD8+ cell effector function were correlated with HBsAg level. Results A positive linear trend between HBsAg level and APRI, liver stiffness (LS), liver transaminases, and HBV VL, and a negative correlation with platelet count were observed. Frequency of cases with HBV-specific CD8+ T-cell proliferation against at least two HBV epitopes was higher in HBsAg < 1,000 IU/ml group. CD8+ T-cell expansion after HBVpolymerase456-63-specific stimulation was impaired in HBsAg > 1,000 IU/ml group, while the response against HBVcore18-27 was preserved and response against envelope183-91 was nearly abolished, regardless of HBsAg level. Cases with preserved HBVpolymerase456-63 CD8+ cell response had lower LS/duration of infection and APRI/duration of infection rates. HBV-polymerase456-63-specific CD8+ T-cell proliferation intensity was negatively correlated with LS/years of infection ratio. Conclusion HBsAg > 1,000 IU/ml HBeAg-negative chronic HBV infection group shows indirect data of higher degree of inflammation, liver stiffness, and fibrosis progression speed, which are related to an impaired HBV-polymerase-specific CD8+ T-cell response.